A New Protocol for Ash Wood Modification: Synthesis of Hydrophobic and Antibacterial Brushes from the Wood Surface - Angelika Macior; Izabela Zaborniak; Paweł Chmielarz; Joanna Smenda; Karol Wolski; Ewa Ciszkowicz; Katarzyna Lecka-Szlachta (Molecules, 2022)
The article presents the modification of ash wood via surface initiated activators regenerated by electron transfer atom transfer radical polymerization mediated by elemental silver (Ag0 SI-ARGET ATRP) at a diminished catalyst concentration. Ash wood is functionalized with poly(methyl methacrylate) (PMMA) and poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) to yield wood grafted with PMMA-b-PDMAEMA-Br copolymers with hydrophobic and antibacterial properties. Fourier transform infrared (FT-IR) spectroscopy confirmed the covalent incorporation of functional ATRP initiation sites and polymer chains into the wood structure. The polymerization kinetics was followed by the analysis of the polymer grown in solution from the sacrificial initiator by proton nuclear magnetic resonance (1H NMR) and gel permeation chromatography (GPC). The polymer layer covalently attached to the wood surface was observed by scanning electron microscopy (SEM). The hydrophobic properties of hybrid materials were confirmed by water contact angle measurements. Water and sodium chloride salt aqueous solution uptake tests confirmed a significant improvement in resistance to the absorption of wood samples after modification with polymers. Antibacterial tests revealed that wood-QPDMAEMA-Br, as well as wood-PMMA-b-QPDMAEMA-Br, exhibited higher antibacterial activity against Gram-positive bacteria (Staphylococcus aureus) in comparison with Gram-negative bacteria (Escherichia coli). The paper presents an economic concept with ecological aspects of improving wood properties, which gives great opportunities to use the proposed approach in the production of functional hybrid materials for industry and high quality sports equipment, and in furniture production.